Learning during the COVID-19 Pandemic: It Is Not Who You Teach, but How You Teach - George Orlov; Douglas McKee; James Berry; Austin Boyle; Thomas J. DiCiccio; Tyler Ransom; Alex Rees-Jones; Joerg Stoye (Institute of Labor Economics (IZA), 2020)
We use standardized end-of-course knowledge assessments to examine student learning during the disruptions induced by the COVID-19 pandemic. Examining seven economics courses taught at four US R1 institutions, we find that students performed substantially worse, on average, in Spring 2020 when compared to Spring or Fall 2019. We find no evidence that the effect was driven by specific demographic groups. However, our results suggest that teaching methods that encourage active engagement, such as the use of small group activities and projects, played an important role in mitigating this negative effect. Our results point to methods for more effective online teaching as the pandemic continues.
Keywords: A22; I23; 330; economic education; pedagogical methods; higher education; COVID-19